(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose – Marketers now understand the importance of gauging customer interest in green products before presenting them to diverse target markets. The objective of the paper is to show how environmental knowledge, concern and responsibility affect households’ attitude towards the purchase of EEHAs in Tirunelveli District. Methodology– This study used a convenience sample of 50 Tirunelvelians aged between 21-60 who were recruited for the study. The tool for the data collection was questionnaire used both in Tamil and English for easy understanding. Using correlation and multiple regression, it was determined whether environmental awareness, environmental concern, and environmental responsibility influenced attitudes toward buying energy-efficient home appliances. Findings – The analysis reveals that the strong positive impact that environment concern, environment knowledge, and environment responsibility have on people’s attitudes toward EEHAs. Practical implications – This article offers vital information for marketers, governmental organisations, and BEE in encouraging energy reduction through eco-friendly applications. These organisations would raise customer awareness and educate them about the advantages of EEHAs.